Optimization of methodology for the extraction of polyphenolic compounds with antioxidant potential and α-glucosidase inhibitory activity from Jamun (Syzygium cumini L.) seeds - M Arivalagan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2021)
Jamun (Syzygium cumini L.) seed is one of the rich sources of polyphenolic compounds​ ​with antioxidant potential and α-glucosidase inhibitory activity. A study was conducted to​ ​optimize the methodology for the extraction of polyphenolic compounds (total phenolic​ ​and flavonoid contents) with antioxidant potential and α-glucosidase inhibitory activity​ ​from Jamun seed powder. The study showed that the nature of solvent and extraction​ ​conditions had a significant effect on total phenolic content (TPC), total flavonoid content​ ​(TFC), antioxidant potential, and α-glucosidase inhibitory activity. The TPC varied between​ ​6.0 (mg/g Jamun seed powder) for the acetone extract to 119.2 (mg/g) for 80% aqueous​ ​acetone extract and TFC varied between 1.06 mg/g for the acetone to 10.81 mg/g for the​ ​80% aqueous methanol. From the study, it was apparent that an aqueous form of acetone​ ​(acetone: water 80:20, v/v) is a better solvent system for extraction of polyphenolic​ ​compounds with high antioxidant potential and α-glucosidase inhibitory activity.​ ​Ultrasonication for 60 min increased the efficiency of phenolic extraction.